Innovation in the family business : succeeding through generations - Schmieder, Joe. (PALGRAVE MACMILLAN, 2014)
"This book is meant to initiate a more definitive conversation about Innovation in the Family Business. Given the dizzying speed of commerce and the bombardment of data in the business world today, this book will contextualize the relevant data and provide a working framework that readers can use to innovate their FBs. The book will utilize the IP from the FBCG team as well as including cases from successful family business ventures such as SC Johnson; Beretta; Mogi (producers of Kikoman) and more. This will be the first book that focuses on innovation in a family business setting"--
"This book will initiate a more definitive conversation about innovation within family businesses. Given the dizzying speed of commerce and the bombardment of data in the business world today, this book will contextualize the relevant data and provide a working framework that readers can use to innovate their family businesses. The author utilizes the IP from the Family Business Consulting Group team as well as includes cases from successful family business ventures such as SC Johnson, Beretta, Mogi (producers of Kikoman), and others. This is the first book to focus on innovation in a family business setting"--
Machine generated contents note: -- Introduction - Creating the Future - Leading Through Innovation -- 1. The Family Difference - Capitalizing on Family Innovation -- 2. Structured Chaos - Creating a Culture of Innovation -- 3. Core Offerings - Driving Value with Product and Service Innovations -- 4. Family Continuity - Applying Innovative Thinking to Succession -- 5. Family Continuity - Applying Innovative Thinking to Governance -- 6. Money and Metrics - Funding and Measuring Innovation -- 7. The Next Generation - Re-Innovating the Family Business -- 8. Moving Innovation Forward - Concluding Thoughts.
Keywords: Family-owned business enterprises; Management -- Technological innovations; Small business -- Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Small Business; Print books